Assessing the added value of group B Streptococcus maternal immunisation in preventing maternal infection and fetal harm: population surveillance study. (17th August 2021) - Lamagni, T; Wloch, C; Broughton, K; Collin, SM; Chalker, V; Coelho, J; Ladhani, SN; Brown, CS; Shetty, N; Johnson, AP
Abstract : Objective: To assess the incidence of maternal group B Streptococcus (GBS) infection in England. Design: Population surveillance augmented through data linkage. Setting: England. Population: All pregnant women accessing the National Health Service (NHS) in England. Methods: Invasive GBS (iGBS) infections during pregnancy or within 6 weeks of childbirth were identified by linking Public Health England (PHE) national microbiology surveillance data for 2014 to NHS hospital admission records. Capsular serotypes of GBS were determined by reference laboratory typing of clinical isolates from women aged 15–44 years. Post‐caesarean section surgical site infection (SSI) caused by GBS was identified in 21 hospitals participating in PHE SSI surveillance (2009–2015). Main outcome measures: iGBS rate per 1000 maternities; risk of GBS SSI per 1000 caesarean sections. Results: Of 1601 patients diagnosed with iGBS infections in England in 2014, 185 (12%) were identified as maternal infections, a rate of 0.29 (95% CI 0.25–0.33) per 1000 maternities and representing 83% of all iGBS cases in women aged 18–44 years. Seven (3.8%) were associated with miscarriage. Fetal outcome identified excess rates of stillbirth (3.4 versus 0.5%) and extreme prematurity (<28 weeks of gestation, 3.7 versus 0.5%) compared with national averages ( P  < 0.001). Caesarean section surveillance in 27 860 women (21 hospitals) identified 47 cases of GBS SSI, with an estimated 4.24 (3.51–5.07) per 1000 caesarean sections, a median time‐to‐onset of 10 days (IQR 7–13 days) and ten infections that required readmission. Capsular serotype analysis identified a diverse array of strains with serotype III as the most common (43%). Conclusions: Our assessment of maternal GBS infection in England indicates the potential additional benefit of GBS vaccination in preventing adverse maternal and fetal outcomes.